Peran Perdagangan International Dan Investasi Terhadap Pertumbuhan Perekonomian Indonesia - Eko Purnomo; Hendra Ibrahim (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
In the context of a country's economy, one of the things that stands out is economic growth. To grow a country's economy, that is by carrying out international trade for a country, such as exports and imports, and making investments. In the context of Indonesia, international trade has become an instrument to encourage economic growth. Meanwhile, investment can increase people's real income, provide greater economic resources for investment (investible surplus), and encourage the rate of economic growth. The type of research carried out is qualitative descriptive research. The data sources used are secondary data originating from journals, books and websites and the data collection technique used is literature study. Based on data from the Central Statistics Agency (BPS), economic growth was below 5% or 4.94% on an annual basis in the third quarter of 2023, this figure is lower than the previous quarter of 5.17% (yoy). This weakness was caused by the decline in export value and imports in the third quarter of 2023. Meanwhile, the role of investment greatly influences economic growth. This result is in accordance with existing theory, where higher investment in a country will increase the country's economic growth. If a country's investment is high, it will contribute to increasing a country's income.